Foresight model inventory (Version 1) - Petsakos, Athanasios; Kruseman, Gideon K. (2022)
This report is part of the documentation component of Work package 3 of the foresight and metrics initiative supporting the Documentation and improved access to standardized, regularly updated, and interoperable versions of CGIAR’s core foresight models, tools, and databases spanning food, land and water systems.